Is adopting full dollarization the solution? Looking at the evidence - Ilan Goldfajn; Gino Olivares (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), Departamento de Economia, 2000)
The paper discusses the advantages and disadvantages of the full dollarization option and offers a few stylized facts and conclusions regarding the effects of full dollarization. On one hand, a full-dollarized economy delivers an impressive inflation performance and may even reduce the impact of external confidence shocks, although not external real shocks. On the other hand, full dollarization does not guarantee fiscal discipline neither the elimination of currency risk precludes default risk or the high volatility of sovereign spreads. In addition, it is not clear whether the reduction in domestic interest rates is the consequence of full dollarization or the competitive internationalized banking system.
Keywords: F30; F41; 330